The SET domain protein Metnase mediates foreign DNA integration and links integration to nonhomologous end-joining repair - Lee, Suk-Hee; Oshige, Masahiko; Durant, Stephen T; Rasila, Kanwaldeep Kaur; Williamson, Elizabeth A; Ramsey, Heather; Kwan, Lori; Nickoloff, Jac A; Hromas, Robert (Proceedings of the National Academy of Sciences - PNAS, 2005)
The molecular mechanism by which foreign DNA integrates into the human genome is poorly understood yet critical to many disease processes, including retroviral infection and carcinogenesis, and to gene therapy. We hypothesized that the mechanism of genomic integration may be similar to transposition in lower organisms. We identified a protein, termed Metnase, that has a SET domain and a transposase/nuclease domain. Metnase methylates histone H3 lysines 4 and 36, which are associated with open chromatin. Metnase increases resistance to ionizing radiation and increases nonhomologous end-joining repair of DNA doublestrand breaks. Most significantly, Metnase promotes integration of exogenous DNA into the genomes of host cells. Therefore, Metnase is a nonhomologous end-joining repair protein that regulates genomic integration of exogenous DNA and establishes a relationship among histone modification, DNA repair, and integration. The data suggest a model wherein Metnase promotes integration of exogenous DNA by opening chromatin and facilitating joining of DNA ends. This study demonstrates that eukaryotic transposase domains can have important cell functions beyond transposition of genetic elements.